Compositional Analysis of the Lignocellulosic Biomass from Agricultural Waste (Rice Husk) - Sheeba Malik; Pramod Kumar Omre; Shreejaya Sivadas (Archives of Current Research International, 2024)
Rice husk, a byproduct of rice milling, represents a significant agricultural waste biomass with untapped potential for various industrial applications. This study provides a comprehensive compositional analysis of rice husk to explore its utility as a valuable resource. The chemical composition of rice husk such as initial moisture content, hemicellulose, cellulose, lignin, ash and extractives were analyzed. The result reported in mean value i.e 9.884 ±0.56 (%) moisture content, 8.077±0.27 (%) extractives, 17.210 ± 0.69 (%) lignin, 21.073 ± 0.62 (%) hemicellulose and 38.640 ± 0.94 (%) cellulose, 15.0 ±0.87 (%) ash. This study concludes that rice husk is an abundant source of cellulose and holds significant potential for cellulose isolation.